2019
DOI: 10.1039/c9qo00942f
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenous cyclonerane sesquiterpenes from an algicolous strain of Trichoderma asperellum

Abstract: Eight new nitrogenous cyclonerance derivatives (1–8) including two unprecedented hydroxamic acids (1 and 2) with potent algicidal activity were characterized from the algicolous fungus Trichoderma asperellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Twentythree signals appeared in the 13 C NMR spectrum (Table 1), ascribed to six methyls, seven methylenes, four methines, and six nonprotonated carbons by DEPT and HSQC data. The above NMR data were very similar to those of deoxycyclonerin B (Song et al 2019), except for the existence of an extra acetyl group, confirmed by the HMBC correlations from H 3 -8′ and H 2 -5′ to C-7′ (Fig. 1).…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…Twentythree signals appeared in the 13 C NMR spectrum (Table 1), ascribed to six methyls, seven methylenes, four methines, and six nonprotonated carbons by DEPT and HSQC data. The above NMR data were very similar to those of deoxycyclonerin B (Song et al 2019), except for the existence of an extra acetyl group, confirmed by the HMBC correlations from H 3 -8′ and H 2 -5′ to C-7′ (Fig. 1).…”
Section: Resultssupporting
confidence: 71%
“…1). On account of the NOE correlation between H-2′ and H 2 -4′ and the similar NMR data with those of deoxycyclonerins (Song et al 2019), the E-geometry was appointed to the vinyl group at C-2′. The relative configurations at C-2, C-3, C-6, and C-7 were certified by the identical 1 H and 13 C NMR data with those of cyclonerane derivatives (Langhanki et al 2014;Laurent et al 1990;Song et al 2018b).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations